Cellular energy sensor SnRK1 suppresses salicylic acid–dependent and –independent defenses and bacterial resistance in Arabidopsis - Linnan Jie; Miho Sanagi; Shigetaka Yasuda; Kohji Yamada; Saki Ejima; Ayumi Sugisaki; Junpei Takagi; Mika Nomoto; Xiu-Fang Xin; Yasuomi Tada; Yusuke Saijo; Takeo Sato (Proceedings of the National Academy of Sciences, 2025)
In nature, plants cope with various pathogens that compete for cellular resources during infection. It has long been suggested that plant defense activity must be linked to cellular energy and metabolic states to optimize the balance between growth and defense. However, the molecular mechanisms that regulate immune activity in relation to cellular energy status remain unclear. Here, we demonstrate that the plant energy sensor SNF1-RELATED KINASE 1 (SnRK1) plays a critical role in modulating defense responses and bacterial resistance in Arabidopsis thaliana . Bacterial elicitor-induced expression of defense marker genes, such as PATHOGENESIS-RELATED 1 ( PR1 ), is significantly repressed under sugar-limited conditions in wild-type seedlings, whereas this expression is markedly enhanced in the snrk1α1i/α2 knockdown mutants. SnRK1 restricts defense-related gene expression and resistance to the biotrophic bacterial pathogen Pseudomonas syringae pv. tomato DC3000, which are partly dependent on salicylic acid (SA). In addition, we found that the SnRK1 kinase activity is increased by high humidity. Consistently, SnRK1 is critical for the suppression of SA-mediated defense responses under high humidity conditions. SnRK1 physically associates with the SA-related transcription factors TGACG SEQUENCE-SPECIFIC BINDING PROTEIN 4 (TGA4) and TGA2 to attenuate PR1 expression. These findings provide valuable insight into the molecular mechanisms linking cellular energy status with immune regulation in plants.